Physical and Chemical Properties of Dry Bottom Ash According to Particle Size Separation for the Development of Light-Weight Artificial Soil - Park, H.I.; Hong, S.R.; Kang, C.; Kim, J.M. (Asian Journal of Chemistry, 2014)
A general method to expand the urban green space is to utilize the artificial ground that is unutilized in cities, such as buildings and rooftops. This artificial ground mainly utilizes light-weight artificial soil that in addition to being light-weight has economic feasibility and functionality. The processing technology of bottom ash in thermal power stations shows a tendency to change from the wet process to the dry process. The dry process bottom ash, which arises from the new process, are expected to be utilized as light-weight artificial soil, because they are poor in water, salt and unburned carbon, which are not the characteristics of the existing wet process bottom ash and have a lower density than general aggregate. Therefore, in this study, the suitability of artificial soil composed of dry process bottom ash was evaluated by comparing it to perlite, which is presently predominantly used as artificial soil. This study shows that the coefficient of permeability, saturation bulk density, pH, EC, total amount of nitrogen and organic matter contents of dry process bottom ash are similar to those of perlite. It is concluded that the dry process bottom ash can be utilized as artificial soil.